Desingularization of implicit analytic differential equations - Cendra, Hernan (2006)
The question of finding solutions to a given implicit differential equation (IDE) is an important one, in part because it appears very naturally in several problems in physics, engineering and many other fields. In this work, we show how to reduce a given analytic IDE to an analytic IDE of locally constant rank. This can be done by using some fundamental results on subanalytic subsets and desingularization of closed subanalytic subsets. An example from nonholonomic mechanics is studied using these methods.